1974
DOI: 10.1159/000122299
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-Automated <i>in vitro</i> Assay for CRF: Activities of Peptides Related to Oxytocin and Vasopressin

Abstract: The CRF-like activity of peptides related to vasopressin and oxytocin was estimated using a semi-automated in vitro bioassay. Rat pituitary halves were incubated for 1 h with the test material in 1.0 ml of Krebs-Ringer bicarbonate buffer. The ACTH released from the pituitary tissue was estimated using adrenal quarters in an automated superfusion system. The pituitary tissue was standardized with median eminence extract, and adrenal tissue was standardizeed with ACTH. Vasopressin and its analogues release ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Vasopressin (VP), which, like CRF, has been localized in cells of the paraventricular nucleus of the hypothalamus (8), also releases ACTH, albeit with less potency than CRF, from anterior pituitary cells in vitro (1,(9)(10)(11)(12)(13) and in vivo in rats (14)(15)(16) and humans (17)(18). Although shown to be an ACTH secretagogue, the physiologic role played by VP in the regulation of ACTH secretion is uncertain (3,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Vasopressin (VP), which, like CRF, has been localized in cells of the paraventricular nucleus of the hypothalamus (8), also releases ACTH, albeit with less potency than CRF, from anterior pituitary cells in vitro (1,(9)(10)(11)(12)(13) and in vivo in rats (14)(15)(16) and humans (17)(18). Although shown to be an ACTH secretagogue, the physiologic role played by VP in the regulation of ACTH secretion is uncertain (3,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CRF and pressor or antidiuretic attivity of various vasopressin analogues is in dispute (16)(17)(18)(19)(20). Recently Aizawa et al found that CRF and pressor activities of several vasopressin analogues were strongly correlated, whereas CRF and antidiuretic activities were hot (21).…”
mentioning
confidence: 99%
“…Because vasopressin has CRF activity [10] and has been reported to be present in the ME [3], one explanation of the experiment described above is that the CRF activity of the column-bound material could be due to the endogenous va sopressin content of the rat ME. Therefore, in order to esti mate the vasopressin content, we determined the pressor ac tivity of rat ME extracts (fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…CRF activity was determined with a semiautomated in vitro bioassay which utilizes rat pituitary halves in a static incubation and adrenal quarters in a continuous superfusion system [10]. In this bioassay, matched sets of rat pituitary halves are incubated first with a standard extract of 1 ME.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation